Letter from Campbell Morfit to James Curtis Booth, June 22, 1859 - Morfit, Campbell (1859)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), sends Booth a half pound of paraffin, describes his new business, and suggests that Booth charge higher fees for his assays and analyses.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897